Estimation of the Sovereign Yield Curve of Peru: The Role of Macroeconomic and Latent Factors - Olivares Ríos, Alejandra (2017)
The study of the yield curve has been a topic that interested economists for a long time since the term structure of interest rates is an important transmission channel of monetary policy to inflation and real activity. In this paper, following Ang and Piazzesi (2003), we study the relevance of macroeconomic factors on Peruvian sovereign yield curve through an Affine Term Structure model for the period from November 2005 to December 2015. We estimate a Gaussian model to understand the joint dynamics of macro variables ―inflation and real activity factors― and Peruvian bond yields in a multifactor model of the term structure. Risk premium are modeled as time varying and depend on both observable and unobservable factors. A Vector Autoregressive (VAR) model is estimated considering no-arbitrage assumptions, which let us to derive Impulse Response Functions and Variance Decompositions. We find evidence that macro factors help to improve the fit of the model and explain a substantial amount of variation in bond yields. Variance decompositions show that macro factors explain a significant amount of the movements in the short and middle segments of the yield curve (up to 50%) while unobservable factors are the main drivers for most of the movements at the long end of the yield curve (up to 80%). Furthermore, we find that setting no-arbitrage restrictions improve the forecasting performance of a VAR and that models that include macro factors forecast better than models with only unobservable components. El estudio de la curva de rendimientos ha sido un tema de interés para los economistas desde hace mucho tiempo ya que la estructura a plazo de las tasas de interés es un importante canal de transmisión de la política monetaria a la inflación y a la actividad real. Usando el enfoque de Ang y Piazzesi (2003), este documento estudia la relevancia de los factores macroeconómicos en la curva de rendimiento soberana Peruana a través de un modelo de estructura afín para el período Noviembre 2005 a Diciembre 2015. Se estima un modelo Gaussiano para entender la dinámica conjunta de las variables macroeconómicas ―factores de inflación y actividad real― y los rendimientos de los bonos Peruanos en un modelo multifactorial de la estructura temporal. Las primas de riesgo se modelan como variables cambiantes en el tiempo y dependen de factores observables y no observables. Asi, se estima un modelo vectorial autorregresivo (VAR) considerando supuestos de no arbitraje, lo que nos permite derivar las funciones impulso respuesta y la descomposición de la varianza del error de predicción. Encontramos evidencia de que los factores macro ayudan a mejorar el ajuste del modelo y explican una cantidad sustancial de la variación en los rendimientos de los bonos. Las descomposiciones de varianzas muestran que los factores macroeconómicos explican una cantidad significativa de los movimientos en los segmentos corto y mediano de la curva de rendimientos (hasta el 50%), mientras que los factores no observables son los principales impulsores de la mayoría de los movimientos al final de la curva de rendimientos (hasta el 80%). Además, encontramos que el establecimiento de restricciones de no arbitraje mejoran el desempeño de pronósticos de un VAR y que los modelos que incluyen factores macroeconómicos pronostican mejor que los modelos con sólo componentes no observables.